EVALUASI ATAS PENGENDALIAN SISTEM INFORMASI AKUNTANSI PENJUALAN PADA PT PENGELOLA PUSAT PERDAGANGAN CARINGIN UNTUK MENGUKUR EFEKTIVITAS DAN EFISIENSI PENGELOLAAN PENDAPATAN LISTRIK - Nano Suyatna (Jurnal Accounting Information System (AIMS), 2018)
In an effort to improve electricity services to customers, there needs to be a balance between the supply of electricity and revenue. Payment methods made by the Perusahaan Listrik Negara (PLN) use Postpaid and Prepaid methods. Because services with postpaid methods better meet customer satisfaction, this method is chosen. Sales Accounting Information System is an information technology-based accounting application to support financial transactions in a company to run faster, more precisely and accurately at a reasonable cost. In its operation, it takes competent human resources to not be a source of problems (human error) and adequate infrastructure. To overcome the obstacles that will arise, whether triggered by the application or by the human resources themselves, it is necessary to control both aspects. Based on this research it shows that the application  of  Sales Accounting Information Systems and existing human resources is sufficiently supportive  and  reliable  in  supporting the creation of good control as it is proven that the level of acceptance of sales targets is realized effectively and efficiently.